Beyonders transcending average leadership - Broeck, Herman Van Den. (Leuven Publishing house LannooCampus, 2012)
In many organisations and countries people are desperately searching for leaders that can provide solutions to transcend the many financial, political and environmental problems that the world is facing. Sadly, such leaders are few and far between. But fortunately there is hope: Beyondership. Leaders who aspire to Beyondershp posses and radiate a deep-seated vision, anchored in a clear set of values. What others see as obstacles, they welcome as challenging opportunities. They create environments that inspire passion, and persevere untill their goals are reached. Even when not supported by powerful parties, they have the courage to be a minority of one and steadfastly fight for what they genuinely believe. For a beyonder, it is not about being the best in the world, but being the best for the world. Beyonders presents a truly unique and challenging framework for all current and aspiring leaders. It points the way to unlocking the real potential for authentic and creative leadership that makes a telling difference. Undoubtedly a book that those who wish to make a real contribution, should read.
Keywords: Leadership